2015
DOI: 10.1007/s10681-015-1609-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs involved in cold tolerance in sweet × field corn

Abstract: Sweet corn was originally due to the recessive allele sugary1 (su1). Sweet corn breeders frequently use field corn genotypes for broadening the narrow genetic base of sweet corn but they have to deal with the reduced viability of su1 plants within some field corn genetic backgrounds. Emergence and seedling vigor are the most critical traits affecting the viability of su1 plants. In two populations of RILs involving sweet corn inbred lines developed from B73×P39 and B73×IL14h, a net natural selection was reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“… Jompuk et al (2005) detected a QTL in this region controlling PSII content of plant under early sowing (low temperature during early spring). The explained phenotypic variance of QTL in mQTL9-1 region varied from moderate in Allam et al (2016) (13.8–18.6%) and in Jompuk et al (2005) (3.6–24.8%) to low in Hu et al (2016) (5.25–8.41%). These results suggest that mQTL9-1 region also contain an important QTL for cold response, which might function at multiple growth stage and exist in multiple genetic background in maize.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“… Jompuk et al (2005) detected a QTL in this region controlling PSII content of plant under early sowing (low temperature during early spring). The explained phenotypic variance of QTL in mQTL9-1 region varied from moderate in Allam et al (2016) (13.8–18.6%) and in Jompuk et al (2005) (3.6–24.8%) to low in Hu et al (2016) (5.25–8.41%). These results suggest that mQTL9-1 region also contain an important QTL for cold response, which might function at multiple growth stage and exist in multiple genetic background in maize.…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies, some QTL have also been identified in this region for cold related traits by using different populations. Fracheboud et al (2002) identified a QTL for CO 2 fixation and PSII of leaves at 15°C from a RIL population; Allam et al (2016) identified a QTL associated ear height of mature plant under low temperature from another RIL population; and Hund et al (2004) identified a root trait QTL using maize seedlings grown at low temperatures. These results indicate that this region might harbor a major gene or several effective genes with pleiotropic effect on maize low temperature response at different growth stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By genomewide association analyses (GWAS), 275 significant loci were associated with the traits, such as number of days from sowing to emergence, relative leaf chlorophyll content, and quantum efficiency of photosystem II, using two panels of 306 dent and 292 European flint maize inbred lines [11]. In another study, two populations of RILs involving sweet corn inbred lines developed from B73 × P39 and B73 × IL14 h were used for mapping under low temperature, and 27 QTLs were linked to increment of days to emergence and F 0 , decrease in dry weight and Fv/Fm in RILs populations of B73 × P39 and 24 QTLs in the RILs populations of B73 × IL14 h [12]. Recently, 159 quantitative trait loci (QTL) for emergence and traits related to early growth were associated by GWAS in 836 maize inbreds under cold treatment [13].…”
Section: Introductionmentioning
confidence: 99%